Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1542/peds.2004-2527
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Rather Than Severity of Sleep-Disordered Breathing as the Major Determinant of Insulin Resistance and Altered Lipidemia in Snoring Children

Abstract: ABSTRACT. Objective. Sleep-disordered breathing (SDB) is associated with insulin resistance and dyslipidemia in adults and in obese children. However, the prevalence of such metabolic abnormalities among snoring children is unknown. This study was done to prospectively assess the relative contribution of SDB and obesity to metabolic disturbances in a large cohort of snoring children.Methods. Measurements of fasting serum glucose, insulin, and lipids were obtained after polysomnographic evaluation in 116 snorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
87
3
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 69 publications
12
87
3
8
Order By: Relevance
“…The subjects in our study had a high level of inflammation, likely due to their severe obesity compared with other study populations. This is consistent with several other studies that found that the BMI, and not measures of OSA, were the primary determinants of insulin resistance 39 and inflammation. 40 Our study is limited by a small sample size.…”
Section: Discussionsupporting
confidence: 92%
“…The subjects in our study had a high level of inflammation, likely due to their severe obesity compared with other study populations. This is consistent with several other studies that found that the BMI, and not measures of OSA, were the primary determinants of insulin resistance 39 and inflammation. 40 Our study is limited by a small sample size.…”
Section: Discussionsupporting
confidence: 92%
“…However, an uncontrolled follow-up study from this group failed to confirm an independent association between SDB and fasting insulin levels, nor did it show consistent associations between treatment of SDB and improvement in metabolic indices (37). Two other reports from pediatric sleep laboratories of young, prepubertal children, including one study that excluded obese children (38), also did not show significant associations between fasting insulin levels and indices of SDB (38,39). In contrast, in our communitybased sample of predominantly postpubertal adolescents, we have demonstrated strong associations of SDB with MetS as well as with individual metabolic parameters commonly associated with MetS, including fasting insulin and the HOMA index.…”
Section: Discussionmentioning
confidence: 75%
“…14 In children, the association of OSA with IR and MetSyn has been inconsistent: some studies have found that OSA increases risk of IR 15 and dyslipidemia, 16 whereas others have found that IR and MetSyn are primarily determined by obesity. 17,18 Most studies have examined associations rather than causal relationships. However, the few interventional studies of metabolic outcome in children with OSA after adenotonsillectomy (T&A, the gold standard pediatric OSA treatment) have had similarly contradictory results.…”
mentioning
confidence: 99%